Origin and evolution of suburban area - Vyacheslav Onufrіеnko (Kazimierz Wielki University, 2018)
The main stages of forming the concept of a suburban strip are considered in the article. The structural elements of the suburban area are considered in more detail. Domestic and foreign specialists, highlighted the leading role of cities in the development of the state, with considerable attention paid to the study of surrounding territories: their territorial coverage (area), functions, interdependence, complementarity of cities and adjacent space.